2011
DOI: 10.1007/s11262-011-0578-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China

Abstract: In this study, suspected classical swine fever (CSF) samples from the Guangxi Province of China were obtained from pigs with acute CSF, aborted fetuses, newborn pigs that died at 1-2 days of age, tonsils of healthy pigs, and leukocytes of immunized sows during 2001-2009. About 92 of 775 samples were found to be positive by RT-PCR, and 41 isolates were obtained. Phylogenetic analysis was performed on the 31 isolates by sequencing the E2 gene, and the isolates were found to cluster into two groups: (1) isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…From Nepal, strains of sub-genotype 2.2 were reported [80]. The situation in China is characterized by high variability of strains that belong mainly to sub-genotypes 1.1, 2.1, 2.2, and 2.3 [81,82,83,84]. Taiwan is also experiencing a change in sub-genotypes.…”
Section: Virus Propertiesmentioning
confidence: 99%
“…From Nepal, strains of sub-genotype 2.2 were reported [80]. The situation in China is characterized by high variability of strains that belong mainly to sub-genotypes 1.1, 2.1, 2.2, and 2.3 [81,82,83,84]. Taiwan is also experiencing a change in sub-genotypes.…”
Section: Virus Propertiesmentioning
confidence: 99%
“…CSFV positive rate in clinical healthy pigs in GuanXi province of Southern China has been reported before, it's about 3% (Luo et al, 2011). The results indicated that C-strain vaccine can exist in pigs for a long period of time after vaccination, and persistently infected clinically healthy pigs exist in different breeding swine farms.…”
Section: Discussionmentioning
confidence: 61%
“…This discrepancy may be due to the shortage of isolate data included in their analysis. Luo et al. (2011) reported that 11 of 31 CSFV isolates belonged to subgroup 1.1.…”
Section: Resultsmentioning
confidence: 99%
“…Groups 1 and 2 are composed of three subgroups (1.1–1.3 and 2.1–2.3) and group 3 of four subgroups (3.1–3.4). Molecular epidemiology studies of Asian CSFV isolates by Japanese (Sakoda et al., 1999), Thai (Parchariyanon et al., 2000), Vietnamese (Kamakawa et al., 2006), Korean (Cha et al., 2007), Chinese (Tu et al., 2001; Deng et al.,2005; Luo et al., 2011; Shen et al., 2011) and Indian (Patil et al., 2010, 2012) researchers have indicated all three genogroups are present in Asia, and within these genogroups, there is considerable diversity.…”
Section: Introductionmentioning
confidence: 99%